Gender-specific information seeking behaviour: A case study of Indian Institute of Public Administration - Khare, Hemant and Bajpai, R.P. (Bihar Journal of Public Administration)
Gender has been one of the most significant issues in study of good governance. Thus, it becomes imperative to investigate the trend of gender specific information seeking in research in public administration. With this view in mind, the present paper intends to highlight the gender specific information seeking behaviour of library users. The library of Indian Institute of Public Administration is one of the richest libraries in the country, so far disciplines in social sciences in general and public administration in particular, are concerned. A large number of scholars visit this library. Hence it ecomes pertinent to take the IIPA Library for the case study. The present paper is an empirical gender study in the context of information science and examines the lopsided nature of the gendered usage of IIPA library. All these have been brought out empirically and objectively. Based on survey of trends of visitors to IIPA library, the present paper finds that greater number of male visitors/users seek information in substantive way than the female visitors. - Reproduced
Keywords: Information needs, Information Seeking Behavior, Gender, Researchers, Visitors, Users, IIPA, Indian Institute of Public Administration, Library, IIPA Library